ADDITION OF VITERNA WITH DIFFERENT DOSAGE ON PELLET FEED ON GROWTH OF GROUPER FISH SEED (Cromileptis altivelis) - Irfan, Muhammad; Nasution, Syafruddin; Nurrachmi, Irvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2020)
This research was conducted from 15 June - 27 July 2019 in the Regional Technical Implementation Unit of The Seawater and Brackish Aquaculture. (UPTD BPBALP Teluk Buo), West Sumatra. This study aim to determine the best of viterna multivitamin right on the growth and the survival of grouper fish (Cromileptis altivelis) seed. The method used in this study was an experimental method using a complete randomized design (RAL) with 4 treatments (A: 0 ml / kg of feed, B: 10 ml / kg of feed, C: 15 ml / kg of feed and D: 20 ml / kg of feed). Parameters in this research are absolute weight growth, absolute length growth, specific growth rate and survival rate. The results of this research are to find out the best viterna multivitamin dose for absolute weight growth was 10 ml / kg of feed, absolute length growth was 10 ml / kg of feed, the specific growth rate was 10 ml / kg of feed and survival rate was 100% of all treatments.